Benang Jahit Operasi dalam Bidang Kedokteran Gigi - Gema Gempita; Nina Djustiana (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2021)
The surgical sutures is one of the main techniques used for wound closure. In the oral cavity, suture are often used after procedures such as tooth extraction, implant surgery, and various oral and periodontal treatment procedures. The purpose of this article is to provide knowledge to readers, especially dentists and academics regarding the function of sutures, general characteristics, as well as various materials of sutures. Suture which are used in dentistry are different from suture used in other areas of the body due to saliva, high vascularity, and other functions in oral cavity such as, speaking, chewing and swallowing. The ideal surgical suture depends on the type of surgery, the location of the wound, and the general condition of the patient. Suture threads that do not match the conditions of the surgical wound and the patient's condition will prolong the healing process and can cause infection. By improving the knowledge about surgical suture, dentists are expected to be able to choose the most appropriate surgical suture based on the patient's condition. In academic terms, by knowing the various choices of surgical suture materials, academics are expected to be able to know the advantages and disadvantages of the sutures which can also inspire them to improve the quality of existing sutures.